Keanekaragaman Jenis Udang Air Tawar di Danau Teluk Kota Jambi (Biodiversity of Freshwater Prawns in Danau Teluk Jambi City) - Daryanto DARYANTO; Afreni HAMIDAH; Winda Dwi KARTIKA (Biospecies, 2015)
The aim of this research is to measure biodiversity of freshwater prawns in Danau Teluk Jambi City. This is a quantitative descriptive research, the samples were taken purposively from three stations. The collected data were analyzed to obtain biodiversity index and dominance index.  Some nvironmental parameters were also measure including temperature, water depth, pH, DO (Dissolved Oxygen), COD (Chemical Oxygen Demand), and BOD (Biochemical Oxygen Demand). The research found 170 individual freshwater prawns belonging to 3 species: Macrobrachium rosenbergi, Macrobrachium lanchesteri, and Macrobrachium sintangense. Biodiversity index (H’) in stations I, II, and III were 0.85, 1.0, and 0.74 respectively and dominance index were 0.51, 0.39, and 0.51 respecytively. The value of physical and chemical water factors of the the three station were: water depth 0.6-2.6 m, temperature 28-31°C, pH 6.49-6.72, BOD 16-20 mg/l, COD 36-43 mg/l, and DO 6.61-6.63mg/l. The result indicated that biodiversity of freshwater prawns in Danau Teluk Jambi City was relatively low  and there was species that dominated the water (Macrobrachium lanchesteri).